Kegiatan Webinar Ramadhan sebagai Momentum Memperbaiki Diri dan Meningkatkan Iman Remaja di Jl. Medokan Semampir, Surabaya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The month of Ramadan is a crucial time for Muslims to strengthen their faith and improve themselves through various religious activities. This community service initiative aims to utilize Ramadan as a means of spiritual development for youth on Jl. Medokan Semampir, Surabaya. The method used in this activity is a participatory approach through the delivery of religious material, interactive discussions, and question-and-answer sessions that actively involve youth. This activity was carried out face-to-face, involving university students as presenters and local youth as participants. The results of the activity showed that the youth showed high enthusiasm in participating in the religious development activities. Through this activity, youth gained a better understanding of the meaning and benefits of fasting in Ramadan and the importance of improving the quality of faith and behavior in daily life. In addition, this activity was able to strengthen social relationships between students and the community and foster religious awareness in youth to be more active in positive activities with religious value. Therefore, the momentum of Ramadan can be used as an effective means to shape religious character and improve the quality of faith of the younger generation in the community.